Lead Acid Battery Costing Under Information Content of Time-Driven Functional Costing Technology (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to apply the complementary relationship of the information content of the costing techniques based on time-oriented functions and its reflection on the leadership of the cost of the acid battery, as this will help solve the research problem represented by the high costs of liquid acid batteries produced in the General Company for Automotive and Equipment Industry - Battery Factory - Bulbul 2 Plant, as a result of not keeping pace with rapid developments and not using cost management techniques and modern manufacturing methods, which led to the inability to compete in the markets, as the costing technique works on the basis of time-oriented functions, which takes into account the requirements of analyzing the functions of the product into its components and analyzing the functions of these components into the functions of the main, secondary, and required secondary components, which helped the unit management to reduce its costs by using practical energy and time equations and excluding or integrating the functions of the secondary components. The research field represented by the General Company for Automotive and Equipment Industry, Babylon 2 Plant, was chosen to apply the research variables to it. In order to achieve the research purpose, the deductive approach was adopted in conducting a survey of the studies that presented the research variables with the aim of extracting ideas and collecting the theoretical foundations presented in books, periodicals, conferences, and related foreign and Arab research, and the inductive approach in linking technologies, with the aim of evaluating the cost system in effect in the factory and reducing costs. The researcher relied on unit data through personal interviews with employees, officials, and managers, direct observation, and visits to the factory employees.